PELATIHAN PEMBUATAN ELEMEN DEKORASI INTERIOR DENGAN TEKNIK ECOPRINT SEBAGAI PENINGKATAN KOMPETENSI SENI GURU DI TK AL ISLAM 5 GROBAGAN - Hapsari, Putri Sekar; Pertiwi, Ayu Ratna; Mumpuni, Primastiti Wening (Abdi Seni, 2025)
This community service program aims to enhance the professional competencies of early childhood educators, particularly in artistic skills, to support the overall improvement of human resources in education. Targeting teachers at TK Al Islam 5 Grobagan, the initiative provides structured training focused on the development of classroom decorative elements using the ecoprint technique. The program responds to existing challenges such as limited knowledge, lack of exposure to ecoprint methods, and insufficient tools and materials. Over a six-month period, participants are trained to create functional and aesthetic items including curtains and table coverings made from primisima and blacu fabrics, as well as wall ornaments crafted from pinewood boards and traditional fans. The ecoprint technique is selected for its creative potential, low production cost, and simplicity, making it suitable for grassroots implementation. Through practical instruction and guided application, teachers are expected to enhance their artistic capacities, integrate creative practices into their teaching methods, and contribute to sustainable, culturally relevant classroom environments. Furthermore, the program fosters design skills that can be applied beyond the educational setting, offering pathways for creative entrepreneurship rooted in local knowledge and materials.